Teacher Illocutionary Speech On Teacher-Student Interaction In Cultivating Character Values Of Vocational School Students - Puspitasari, Hestri Afri; Rustono, Rustono; Baehaqie, Imam (Universitas Negeri Semarang, 2022)
Vocational students enter the period of searching for identity, there are many new things they want to try. Therefore, instilling character in them needs to be done. This is one of the efforts in shaping the character of students who have good character. This research was conducted to describe the character values ​​contained in the illocutionary utterances of the teacher in coaching activities for inculcating the character values ​​of SMK students.This study uses a pragmatic research approach with a research focus on teacher illocutionary speech in coaching activities in instilling character values ​​in vocational students. The data collection technique in this study is the listening technique and the note-taking technique. This research is expected to be an evaluation material for the Homeroom teacher in speaking so that it can have a good influence on students. The results showed that the teacher's speech in the teacher-student interaction contained the values ​​of honest, responsible, independent, religious, and mutual cooperation characteristics.